Effevtiveness Health Education Using Audio Visual With Lectures And Poster With Lectures Of Changes In Behavior Selection Of Snacks In Tulungagung Elementary School - Riyani, Anis; Nurwijayanti; Yeny Hidajaturrokhmah, Nur (Journal of Global Research in Public Health, 2019)
Selection of snacks is the embodiment of behavior. To change behavior which is well lit can start with giving information to increase the knowledge of the child so it will be awareness and causing changes in behavior. The purpose of this research was to analyze the differences health education using audio visual with lectures and poster with lectures of changes in behavior selection of snacks on the fifth grade in 1 and 2 Kenayan Tulungagung Elementary School. The research design was quasy experimental design by non-equivalent control grup. The population is all the students snacks on the fifth grade in 1 and 2 Kenayan Tulungagung elementary school with a sample of 78 respondents on total sampling. The data obtained from the kuesioners and processed by using wolcoxon statistic and mann-whitney. The result of the research, half more of the respondents by using audio visual is in the good category that 28 respondents (72%), and half of the respondents by using poster media is in the good category that 19 respondents (48,7%). Statistical test result obtained P value 0,022 < α 0,05 then H0 is rejected and H1 is accepted which means there is a differences health education using audio visual with lectures and poster with lectures of changes in behavior selection of snacks on the fifth grade in 1 and 2 Kenayan Tulungagung Elementary School. Health education using audio visual is more effective in changing the behavior of child snacks election because in audio visual not just using images but also using sound.